2022
DOI: 10.36923/jicc.v22i4.60
|View full text |Cite
|
Sign up to set email alerts
|

Incorporated Tri Pramana Philosophy on Learning Science in Elementary School Culture

Abstract: Tri Pramana, which is constituted of two major components, denotes the three life strengths to comprehend and believe in a certain event in Bhuwana Alit with manacikapura as the three powers of living beings, including (1) Bayu as the breath power, (2) Sabda as the sound power, and (3) Idep as the mind power. As delineated in Widhi Tatwa, Tri Pramana encompasses Praktyaksa Pramana, Anumana Pramana, and Agama Pramana (Sabda Pramana), which are possessed by humans, the most flawless life forms to realistically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…The leadership is also seen to be connected with some other cadet members; in other words, the leadership does not only want to talk and discuss with certain people so that there is no clustering among cadet members. This is in accordance with the findings of Suranata et al (2022), who found that autocratic leadership style has a positive and significant effect on work discipline at the Bali Province Language Center, as well as the findings of Suhartono et al (2023), who found that leadership style has an effect on employee work discipline at the Tasikmalaya education office.…”
Section: Discussion Leadership Style On Cadet's Attitudessupporting
confidence: 92%
See 1 more Smart Citation
“…The leadership is also seen to be connected with some other cadet members; in other words, the leadership does not only want to talk and discuss with certain people so that there is no clustering among cadet members. This is in accordance with the findings of Suranata et al (2022), who found that autocratic leadership style has a positive and significant effect on work discipline at the Bali Province Language Center, as well as the findings of Suhartono et al (2023), who found that leadership style has an effect on employee work discipline at the Tasikmalaya education office.…”
Section: Discussion Leadership Style On Cadet's Attitudessupporting
confidence: 92%
“…Field Suranata et al (2022) conducted research to find the effect of leadership style on work discipline. In Darmawan and Putri (2017), research was conducted to see the effect of leadership style on organizational commitment.…”
mentioning
confidence: 99%